Gender Perspective in International Environmental Law About Access to Drinking Water - Minaverry, Clara María; Cáceres, Verónica Lucía (Ius Humani. Jornal do direito, 2026)
This paper focuses on the incorporation of a gender perspective in international environmental law, specifically in relation to the human right of access to safe drinking water. Using a qualitative approach and through a documentary analysis of environmental instruments elaborated by international organizations, the study examined the existing legal advances and gaps regarding the principles of equality and intersectionality. The results of the paper show that, although the international community has progressively recognized the centrality of water as a human right, the gender dimension remains marginal. It is therefore concluded that the effective incorporation of this perspective is essential to ensure equity, sustainability, and the fulfillment of international commitments regarding human rights and the environment, which is also crossed by the reality of climate change.